EDUCATION OF THE SPIRITUAL QUALITIES OF STUDENTS IN TEACHING MILITARY HISTORY COURSES (American Journal of Interdisciplinary Research and Development, 2023)
One of the most important conditions for the implementation of the educational and educational tasks set before the history course is the place of the history course taught in each class, its educational and educational tasks, the topics of each section and section, it is appropriate to start teaching history only after the sub-tasks of the subject taught in each lesson have been clearly defined in advance.